Building a Resilient Healthcare Workforce: Strategies for Retaining and Developing Health Assistants and Nursing Technicians in Line with Saudi Arabia’s Vision 2030 - Bunyan Matar Alhariji, Shafi Eidan Aldhafeeri, Fahd Salman Aid Al-Badali, Abdullah Saadah Sulaiman Alhurayji, Salman Ayed Alhurayji, Mohammed Fahad Aldhafeeri (Journal of International Crisis and Risk Communication Research, 2024)
Saudi Arabia's Vision 2030 strategic plan aims to transform and enhance the healthcare system to meet the evolving needs of its population. A key component of achieving this goal is developing a skilled, resilient, and sustainable health workforce. Health assistants and nursing technicians play crucial roles in delivering quality patient care and supporting the functioning of healthcare facilities. However, high turnover rates and skill gaps among these frontline workers pose significant challenges. This paper examines strategies for retaining and developing health assistants and nursing technicians in Saudi Arabia to build a resilient healthcare workforce aligned with Vision 2030 objectives. A literature review was conducted using PubMed, Scopus, and Saudi Digital Library databases to identify relevant studies. The findings suggest that implementing targeted retention interventions, such as competitive compensation, opportunities for career advancement, and supportive work environments, can reduce turnover intentions among health assistants and nursing technicians. Furthermore, investing in competency-based training programs, interprofessional education, and continuous professional development can enhance their skills and readiness to meet the demands of a transformed healthcare system. The paper concludes with recommendations for policymakers, healthcare leaders, and educators to adopt a multi-faceted approach to workforce retention and development, including establishing career pathways, promoting work-life balance, fostering a culture of recognition, and collaborating with educational institutions to align training with workforce needs. Implementing these strategies can contribute to building a resilient healthcare workforce capable of delivering high-quality care and achieving the healthcare goals of Saudi Arabia's Vision 2030.